1994
DOI: 10.2136/sssaj1994.03615995005800050027x
|View full text |Cite
|
Sign up to set email alerts
|

Root‐Zone Mineral Nitrogen Changes as Affected by Crop Sequence and Tillage

Abstract: C ROP SEQUENCE AND TILLAGE should be employed so that N mineralization is synchronized with subsequent crop N uptake. Improving N utilization reduces potential NO3 leaching into the groundwater from agricultural fields. The amount of NO 3 leaching out of the root zone is a function of the NO3 concentration in the root zone and the water flux through this zone.Large amounts of N are mineralized after alfalfa is killed, especially the first year. Fox and Piekielek (1988) reported that 70, 20, and 10 % of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…We estimated net N mineralization during and after the wheat's growing season from all but the conventionally fertilized treatment using the buried bag method of Lentz and Lehrsch (2012a) that was adapted from ones described by Westermann and Crothers (1980) and Meek et al (1994). In brief, the method utilizes polyethylene film, permeable to oxygen (O 2 ) and carbon dioxide (CO 2 ) but nearly impermeable to water vapor, to encase moist soil collected from and then replaced within a few hours into the soil profile from whence it came.…”
Section: Field Operations For Winter Wheatmentioning
confidence: 99%
“…We estimated net N mineralization during and after the wheat's growing season from all but the conventionally fertilized treatment using the buried bag method of Lentz and Lehrsch (2012a) that was adapted from ones described by Westermann and Crothers (1980) and Meek et al (1994). In brief, the method utilizes polyethylene film, permeable to oxygen (O 2 ) and carbon dioxide (CO 2 ) but nearly impermeable to water vapor, to encase moist soil collected from and then replaced within a few hours into the soil profile from whence it came.…”
Section: Field Operations For Winter Wheatmentioning
confidence: 99%
“…We used a buried-bag method adapted from Westermann and Crothers (1980) and Meek et al (1994) to measure net N mineralization in plot soils. In each plot, four 5.7-cm-diameter soil cores, 0 to 30 cm deep, were collected, composited, and passed through a 0.4-cm screen.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…Hanselman et al (2004) compared several methods for measuring net N mineralization rates and found that buried bags (Eno, 1960) gave good results until the plastic fi lm lost its integrity (>45 d). In southern Idaho irrigated soils, researchers using a polyethylene bag that diff ered from that of Hanselman et al (2004) achieved good results when the bags were buried for as long as 150 d Crothers, 1980, 1993;Meek et al, 1994;Lentz et al, 2011).…”
mentioning
confidence: 99%
“…Of the field methods, the buried bag technique of Lentz and Lehrsch (2012a), as adapted from Eno (1960), gives representative estimates of in situ net N mineralized for the region's irrigated soils (Westermann and Crothers 1980;Meek et al 1994;Lentz et al 2011). The technique utilizes polyethylene film, permeable to O 2 and CO 2 but nearly impermeable to water vapor, to encase moist soil collected from, then replaced within a few hours into cavities in the soil profile.…”
Section: Introductionmentioning
confidence: 99%